Anthropogenic impact in the Maya Lowlands of Petén, Guatemala, during the last 5500 years. (15th February 2018) - Battistel, D.; Roman, M.; Marchetti, A.; Kehrwald, N. M.; Radaelli, M.; Balliana, E.; Toscano, G.; Barbante, C.
ABSTRACT: Trace and rare earth elements from a sediment core from Lake Petén Itzá (Guatemala) depict the geochemical dynamics affecting the lake from ∼5500 a BP to the present. This timing encompasses the Preclassic (4000–1700 a BP) and Classic Periods (1700−1000 a BP) when thriving Maya societies extensively cleared land for agriculture. We demonstrate that this land use occurred during times of increased precipitation, where both processes resulted in increased erosion. Rare earth element ratios depict high precipitation rates between 3000 and 1000 a BP, correlating with an increase in allochthonous silicate input and low organic carbon in the 'Maya Clay' stratigraphic section, where this layer is ascribed to intensive anthropogenic land use. Cesium anomalies provide additional evidence for runoff due to high rainfalls and amplified by anthropogenic impacts. The Petén Itzá core contains anomalous spikes of arsenic and mercury, and these peaks correspond to documented volcanic eruptions and therefore are probably natural. The geochemical composition of sediments and palynological records indicate re‐growth of the forest after ∼900 a BP. This increased forest vegetation coincides with the timing of the decline in Maya agriculture.